Lacustrine deltas and subaqueous fans: almost the same, but different – a review - Gruszka, Beata; Zieliński, Tomasz (Geologos, 2021)
Although deltas and subaqueous fans are both formed in the same near-shore zones of basins, the hydraulic conditions for their formation, development and sedimentary records are different. The present review discusses the results of previously published studies of fan deltas (Gilbert-type deltas) and subaqueous fans of lacustrine and glaciolacustrine environments. The depositional mechanisms of deltas and subaqueous fans, textural and structural features of the lithofacies associations and their typical lithofacies are presented. The characteristics of subaqueous fans, which are still relatively poorly understood and are often overlooked in sedimentological interpretations of lacustrine sedimentary successions, receive particular attention. The palaeoenvironmental and lithological differences between deltas and sub-aqueous fans are highlighted.